Estudo do comportamento mecânico das ligas de titânio beta metaestável TMZF e Ti15%Mo durante processamento termomecânico - Guerra, Ana Paula de Bribean (2020)
Stress-strain curves of two metastable beta titanium alloys, the Ti-15%Mo alloy and the TMZF alloy were evaluated. The curves were obtained from isothermal hot compression tests in a temperature range from 650 to 900 ° C, strain rates between 0.172 and 17.2 s-1 and also under continuous cooling. Hardening and softening phenomena that occurred during hot deformation were evaluated by means of stress x strain curves and microstructural analyzes. Based on the obtained data, constitutive equation’s constants of phenomenological models available in the literature were determined in order to evaluate their stress prediction ability. The evaluated models were the strain compensated Arrhenius equation model, modified Johnson-Cook model and modified Zerilli-Armstrong model. From the microstructural analyzes of the deformed samples, the occurrence of dynamic recovery phenomena was very pronounced, delaying the occurrence of dynamic recrystallization for the highest temperatures under the analyzed conditions. Through the energy dissipation efficiency maps and deformation instability maps it was possible to delimit regions of improved processing efficiency within the evaluated processing conditions. The athermic omega phase was present in all deformed samples; there was no alpha phase precipitation during deformation. It was not possible to obtain a processing condition that would make possible a completely recrystallized microstructure constituted by the beta phase for any of the processing conditions, since the regions of the analyzed samples did not show homogeneity and the recovery by formation of sub-grains occurred preferably in grain boundary regions, where a high density of dislocations was detected.